The Spectrum and Aetiology of Mycotic Infections from a Tertiary Care Hospital from Western Part of India - Gandham, Nageswari Rajesh (JCDR Research and Publications (P) Limited, 2013)
Background: In the past few years, there has been an increase in infections caused by fungal aetiology. This is mainly due to increase in sizes of populations which are at risk. Also, fungi which were previously considered as non-pathogenic have been increasingly implicated. Hence, this study was taken up. Aim: To assess the magnitude of mycotic infections in this set up. To assess the spectrum of fungi which are involved in various infections. Material and Methods: Total 704 samples taken over two and half period were included. They consisted of various samples like sputum, blood, urine, sterile body fluids, corneal scrapings. These were processed by conventional mycological techniques. These included direct microscopy after Gram staining and KOH mount, culture on Sabouraud’s dextrose agar (SDA), corn meal agar, brain heart infusion (BHI), brain heart infusion agar (BHIA) and others, as required. For non-albicans Candida, the automated Vitek 2 C system was used. Various moulds and yeasts were identified up to genus level and species level. Results: Of 704 samples, 336 (48%) were positive for fungal culture. Of these, 244 isolates were yeast like fungi, 81 were moulds, 7 were yeasts and 4 were dimorphic. Among blood stream infections, non-albicans Candida were the commonest isolates. In the urine samples, C. albicans was the commonest isolate. From corneal scrapings, only moulds and dimorphic fungi were isolated. Conclusion: Incidence of non- albicans Candidal infections is increasing. Culture and identification of mycotic infections is essential for commencement of suitable antifungal therapy.